Prodromi costituzionali e regolamentazione emergenziale. Un’analisi de iure condendo (Società e diritti, 2023)
Parole chiave: Costituzione, emergenza, leale collaborazione, autonomie locali, pubblica amministrazioneAbstractThree years after the beginning of the Covid-19 pandemic, it is possible to make an analysis of the consequences that the pandemic has generated on the constitutional order, with particular regard to the regulatory choices adopted to deal with the pandemic itself. The aim of this work is to examine the events, including the proliferation of "emergency" administrative acts, which concerned the impact of the "pandemic" regulation upon the constitutional system, both in reference to State-Regions relations and the system of sources, as well as to the limitation of the rights of the individuals. The state legislature has intervened in harmony with the constitutional framework, even in the presence of certain critical issues, especially with regard to the application of certain principles of administrative law with an acclaimed "participatory" intent such as adequacy and loyal collaboration.